PENGARUH KAPABILITAS ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KEMANDIRIAN PENGELOLAAN ORGANISASI - KHABIB ALIA AKHMAD (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
The development of MSMEs in Indonesia cannot be separated from the roles of other parties that help develop MSMEs. One of the institutions in Indonesia that plays a role in the development of MSMEs is the Business Development Services Provider (BDS-P). BDS-P is a company, institution or individual that provides services to MSMEs which have a planning function, an implementation function and a development function. The purpose of this research is to see the extent to which organizational capabilities and organizational culture have an influence on the independence of organizational management. In this study, a survey method was used by distributing closed and open questionnaires. The analysis technique used in this study is path analysis. It can be concluded that BDS-P capability affects the independence of BDS-P management, and organizational culture affects the independence of BDS-P management.